Pengaruh Work-Life Balance terhadap Profesionalisme melalui Mediasi Kepuasan Kerja pada Aparatur Sipil Negara (ASN) di Lingkungan Pemerintah Kabupaten Tapanuli Selatan - Sri Wahyuni Harahap; Kaiman Turnip; Rahmi Lubis (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
The aim of this research is to analyze the mediating role of job satisfaction in the relationship between work-life balance and the professionalism of ASNs. These two factors are critical to study because an imbalance between work and life may result in unprofessional behavior, and job dissatisfaction may also lead to unprofessionalism at work. The study utilized quantitative research methods, employing Structural Equation Model (SEM) data analysis techniques using AMOS version 22 software. Stratified random sampling was used to select 300 ASNs as respondents, and data were collected using professionalism, work-life balance, and job satisfaction scales. The results indicated that job satisfaction significantly mediated the relationship between work-life balance and professionalism. This study highlights the importance of job satisfaction as a mediator in maintaining the professionalism of ASNs and suggests the need for policies to improve work-life balance in order to enhance professionalism in the workplace. Relevant keywords include job satisfaction, work-life balance, professionalism, ASNs, and Structural Equation Model.